Classroom assessment concepts and applications - Russell, Michael K. 1967- (McGraw-Hill, 2012)
"Assessment is a daily, ongoing, integral part of teaching and learning. Classroom Assessment: Concepts and Applications explores how assessment is a key component of all aspects of the instructional process, including organizing and creating a classroom culture, planning lessons, delivering instruction, and examining how students have grown as result of instruction. The text also introduces preservice teachers to new tools and approaches to classroom assessment that result from the infusion of computer-based technologies in schools. This is the most teacher friendly assessment textbook available one that will inform a teachers assessment practices for years to come."--Provided by publisher.